Synthesis of Some New Polysiloxane Ligand System (Iminodiacetate) Part I - Parish, R.V.; EL-Nahhal, I.M.; EL-kurd, H.M.; Baraka, R.M. (Asian Journal of Chemistry, 2010)
The polysiloxane-immobilized glycinate and immodiacetate chelating ligand system of the general formula Ⓟ-(CH2)3N(CH2CO2H)2 (where Ⓟ represents the polysiloxane network), have been prepared by the reaction of 3-halopropyltrimethoxysilane before or after its hydrolytic polycondensation with tetraethoxysilane and diethyliminodiacetate HN(CH2CO2Et)2. The elemental analyses indicate that the replacement of iodine by diethyliminodiacetate ligand groups takes place much easier than chlorine. The iminodiacetate polysiloxane ligand systems show high potential for copper(II) uptake and form 1 : 1 complexes with copper(II).